2016
DOI: 10.1016/j.jorganchem.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated poly-ynes and poly(metalla-ynes) incorporating thiophene-based spacers for solar cell (SC) applications

Abstract: Solar cells (SCs) are of considerable current research interest because of their potential as a clean alternative to fossil fuels. Researchers across the globe are developing novel polymeric materials with enhanced power conversion efficiency (PCE). Conjugated poly-ynes and poly(metalla-ynes) incorporating late transition metals and thiophene-based spacers have played a very important role in this strategic area of materials research. The performance of the SCs can be optimized by varying the conjugated spacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 174 publications
1
19
0
Order By: Relevance
“…A focus on discrete molecular complexes will be maintained, readers specifically interested in the use of metal containing polymers are directed to relevant literature. [93][94][95][96] Studies of complexes of a range of metals will be presented and are organized according to their group in the periodic table.…”
Section: Methodsmentioning
confidence: 99%
“…A focus on discrete molecular complexes will be maintained, readers specifically interested in the use of metal containing polymers are directed to relevant literature. [93][94][95][96] Studies of complexes of a range of metals will be presented and are organized according to their group in the periodic table.…”
Section: Methodsmentioning
confidence: 99%
“…Benzothiadiazole (BTD) is a well-known strong electron-acceptor and is used to develop highperformance donor-acceptor (D-A) materials. BTD-containing materials often possess low band gaps, intense absorption, and emission that extends to the visible to near infrared (NIR) region, and thus are considered as unique materials for opto-electronics (O-E) and other applications [52]. Besides, it has also been reported that HOMO-LUMO energy levels of N^C-chelate organoboron compounds Benzothiadiazole (BTD) is a well-known strong electron-acceptor and is used to develop high-performance donor-acceptor (D-A) materials.…”
Section: -Arylthiazole and Aminobenzothiadiazole Derived N^c-chelatesmentioning
confidence: 99%
“…All other bond parameters were found to be within the expected ranges for dimeric Pt(II) diyne complexes. [11][12]…”
Section: Structural Characterizationmentioning
confidence: 99%
“…The intramolecular bond parameters in M2 are similar to those in M1, and in related dinuclear diplatinum complexes. [11][12] Optical-absorption spectroscopy The room temperature solution absorption spectra of the Pt(II) di-ynes (M1-M3) and…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation